2022
DOI: 10.1007/s10753-022-01684-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Species Associated with Highly Allergenic Plant Pollen Yield a High Level of Endotoxins and Induce Chemokine and Cytokine Release from Human A549 Cells

Abstract: Sensitization to pollen allergens has been increasing in Europe every year. Most studies in this field are related to climate change, phenology, allergens associated with different pollens, and allergic disorders. As a plant microhabitat, pollen is colonized by diverse microorganisms, including endotoxin-producing bacteria which may contribute to pollen allergy (pollinosis). Therefore, bacteria isolated from high allergenic and low allergenic plant pollen, as well as the pollen itself with all microbial inhabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…This possible higher allergic potential is caused by a high lipopolysaccharide concentration (LPS) concentration of the bacteria on the pollen. Interestingly, strain Bol-Pol-6 T has one of the highest measured LPS concentrations in this study with an LPS concentration of 76.6 ng l −1 [ 47 ] and five next relative uncultured bacteria (pairwise similarity values 98.72–99.70%) found in floor dust (FM872738) [ 48 ] and on human skin (HM270658, HM270467, JF167742, JF152894) [ 49 ] are also associated to allergic reaction in these studies.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This possible higher allergic potential is caused by a high lipopolysaccharide concentration (LPS) concentration of the bacteria on the pollen. Interestingly, strain Bol-Pol-6 T has one of the highest measured LPS concentrations in this study with an LPS concentration of 76.6 ng l −1 [ 47 ] and five next relative uncultured bacteria (pairwise similarity values 98.72–99.70%) found in floor dust (FM872738) [ 48 ] and on human skin (HM270658, HM270467, JF167742, JF152894) [ 49 ] are also associated to allergic reaction in these studies.…”
Section: Resultsmentioning
confidence: 93%
“…Compared to insect-pollinated pollen species (autumn crocus and rape), birch pollen possesses significantly higher species richness and different communities [ 15 ]. Furthermore, it was shown that bacteria and pollen from wind pollinated plants like birch could have a higher allergic potential [ 47 ]. This possible higher allergic potential is caused by a high lipopolysaccharide concentration (LPS) concentration of the bacteria on the pollen.…”
Section: Resultsmentioning
confidence: 99%
“…Also, other factors than endogenous properties of pollen may contribute to their immunomodulatory potency. For example, pollen may contain microbial components [ 31 33 ]. In the study by Obersteiner et al [ 31 ], allergenicity of birch was correlated with the high bacterial diversity on pollen.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Obersteiner et al [ 31 ], allergenicity of birch was correlated with the high bacterial diversity on pollen. Manirajan et al [ 33 ] noticed that high allergenic plant pollen (e.g., birch) had a higher amount of endotoxins compared to low allergenic plant pollen. Endotoxins, also called as LPS, are the component of the outer membrane of Gram-negative bacteria and recognized by TLR4 on innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that began to be deeply investigated is the involvement of pollen-associated microbes in medical issues, more specifically their potential role in the sensitization to the widespread pollen-originating allergic rhinitis (Obersteiner et al, 2016 ; Ambika Manirajan et al, 2022 ) or the effect of propolis used in traditional medicine. On the contrary, the possible implications of pollen as one source of seed microbiome have so far been largely neglected, i.e., the pollen–microbe–seed system has not been investigated yet, as have the microbiomes of other plant habitats (such as the rhizosphere and phyllosphere).…”
Section: Pollen- and Seed-associated Microbiomementioning
confidence: 99%